Why Even Kantian Angels Need the State: Comments on Robert Hanna’s “Exiting the State and Debunking the State of Nature” - Baxley, Anne Margaret (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Against a widely-held interpretation of Kant’s political philosophy, according to which Kant holds that all finite rational beings have an innate right to freedom as well as a duty to enter into a civil condition governed by a social contract in order to preserve that freedom, Robert Hanna contends that Kant is in fact an anarchist. Hanna’s argument for his novel thesis that Kant ultimately views the State as an unjustifiably coercive institution that should be eliminated depends heavily on the claim there is an outright conflict between Kant’s political theory in The Doctrine of Right and Kant’s ethics. I argue that we should resist Hanna’s provocative claim that Kant’s ethics directly falsifies his official political theory. Further, I suggest that even morally autonomous Kantian angels need the State to guarantee the protection of their external freedom and to promote justice.